Publicistic Articles Of Soviet Writers About Robert Burns And His Creativitive Works In The Periodicals Of 1930–1970 Years - N. Zhatkin, Dmitry (2019)
The articles about Robert Burns and his creative works, written by Soviet writers and published on the pages of Russian periodicals (mainly newspapers) in the 1930s and 1970sare firstly systematized and comprehended in the article. An article written by V.I. Lebedev-Kumach, «The Great Singer of the Scottish People», published in the «Literary Newspaper» on August 15, 1938 became the first material of this kind. This article, which appeared along with the first translations of S.Ya. Marshak, invoked Russian readers to get acquainted and to fall in love with Burns, a wonderful lyric poet and master of songs, at the same time, skillfully placing emphasis on certain aspects of the poet’s creative works - his nationality, cheerfulness, love of nature. The poet and translator M.A. Zenkevich in his article «The Scottish Songwriter» (1946), in contrast to V.I. Lebedev-Kumach, focused on the social significance of Burns' works, pointed out the poet's interest to the revolutionary liberation movement, called him «a convinced democrat, a fighter for equality and brotherhood of all working people»,noted that the poet's work is imbued with «deep humanity». The articles of A.A.Surkov «In the Land of Burns» (1953) and B.N. Polevoy «In the Homeland of Robert Burns» (1955) reflect the impressions of Soviet writers after a trip to Scotland, visiting of memorial places associated with the name of Burns. If A.A.Surkov chose a lyric tone for his article, then B.N. Polevoy picked out political and social aspects, speaking about the consonance of «great ideas of love for workers, ideas of freedom, peace and friendship of peoples» to the Soviet people, the desire of the Soviet Union «to expand and strengthen cultural ties with all nationalities». In the profound article of A.E. Adalis, «The National Poet» (1959), the edition of the classic collection of Marshak’s translations from Burns becomes only an informational reason for the appearance of subsequent deep reflections about the «royal poet» Burns, noble, proud, generous, able to be generous and at the same time sizzling contempt for wealth and nobility. An example of the late Soviet reception of the Burns image can be considered by taking into account the article written by L.N. Vasilyeva «On the day when Robin was born...» (1978), in which the poet’s bright personality, his elements of Scottish color (bagpipes, hot haggis) free and fun atmosphere of Burns festivities, in which Moscow schoolchildren «Friends of Scotland Clubs» are participated took the first place. More than others, Burns was written about by his most famous translator S.Ya. Marshak, to whom three journalistic articles and an open letter published in 1956–1960in the newspaper «Pravda», «Literary newspaper» and the magazine «Education» are belonged. In these articles you can see the impressions of his trips to Scotland, and a valuable response to the creative activities of the predecessors who popularized Burns (in particular, M.Yu. Lermontov, M.L. Mikhailov, E.G. Bagritsky, T.L. Schepkina-Kupernik), and judgments, revealing the originality of the creative laboratory of S.Ya. Marshak, as a translator of Burns, and a holistic view on the creative personality of the great Scottish author.